ভাসানী আদর্শ পুনরুত্থান : (Rejuvenate Moulana bhashani center through the revival of his philosophy) - Khan, Sohana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2021.